1995
DOI: 10.1111/j.1095-8649.1995.tb05984.x
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory growth in Alaska yellowfin sole, Pleuronectes asper, following food deprivation

Abstract: During the early spring four groups of sub-adult Pleuronectes asper were fasted for either 0, 2, 4 or 6 weeks at the beginning of a 12-week experiment, then fed to satiation to examine their ability to compensate with faster growth after food deprivation. All fish increased their stored energy reserves markedly and at the end of the experiment all four groups had similar body energy content (J g-I), length gains and dry weight to wet weight ratios. The groups of yellowfin sole fed continuously or fasted for 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 14 publications
2
45
1
3
Order By: Relevance
“…Partial compensatory growth (when fish submitted to feed deprivation and refeeding regime and do not achieve the same body mass as those fed continuously) (Paul et al, 1995), was reported in fish that were subjected to 2 days deprivation / 4 days refeeding cycle. In accordance with our study, Christensen and McLean (1998) reported that compensatory growth was also demonstrated in the same fish (O. mossambicus).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Partial compensatory growth (when fish submitted to feed deprivation and refeeding regime and do not achieve the same body mass as those fed continuously) (Paul et al, 1995), was reported in fish that were subjected to 2 days deprivation / 4 days refeeding cycle. In accordance with our study, Christensen and McLean (1998) reported that compensatory growth was also demonstrated in the same fish (O. mossambicus).…”
Section: Discussionmentioning
confidence: 99%
“…This strategy is believed to take advantage of a phenomena called compensatory growth, which is described as an accelerated growth rate resulting from an appropriate refeeding of the fish after a period of feed restriction or exposure to unfavorable conditions such as low temperature, low oxygen, and reproductive effort (Ali et al, 2003). Compensatory growth can be classified as over-compensation (Hayward, Noltie, & Wang, 1997), complete-compensatory (Jobling, Koskela, & Winberg, 1999) or partial compensation (Paul, Paul, & Smith, 1995), and it depends on the species, the duration, and severity of the process (Tian & Qin, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Gaylord & Gatlin 2001). Most research on the capacity for compensatory growth has examined responses to periods of food restriction or deprivation (Jobling et al 1994, Paul et al 1995, Sogard & Olla 2002. However, compensatory feeding and growth responses have also been observed in response to growth reductions resulting from oxygen depletion (Bejda et al 1992, Foss & Imsland 2002, delay in diet switch (Buckel et al 1998), and reduced temperatures (Mortensen & Damsgård 1993, Nicieza & Metcalfe 1997.…”
Section: Abstract: Pacific Halibut · Hippoglossus Stenolepis · Thermmentioning
confidence: 99%
“…O papel da temperatura na regulação da alimentação e crescimento é pouco descrito em peixes, mas sabe-se que a maioria deles se alimenta melhor (Paul et al, 1995) e as taxas de crescimento tendem a ser mais altas (Dobson & Holmes, 1984), na primavera e verão.…”
Section: Introductionunclassified
“…O retorno às condições adequadas de alimentação, após um período de inanição ou má nutrição, promove um crescimento rápido no animal, chamado crescimento compensatório (Dobson & Holmes, 1984;Paul et al, 1995;Xie et al, 2001). O crescimento compensatório em peixes pode ter importante aplicação na aqüicultura (Quinton & Blake 1990;Hayward et al, 1997).…”
Section: Introductionunclassified